The Effect of Experiential Marketing, Perceived Quality, as Well Advertising of Purchase Decisions (Study on Wardah Cosmetics User in Kadipaten District) - Haris Fauzi (Institute of Computer Science (IOCS), 2021)
Purchasing decisions are very important in marketing. Users who fail in deciding theirpurchase, this is found by several factors. This study aims to see the effect of Experimental Marketing, Perceived Quality and Advertising on purchasing decisions for users of Wardah Cosmetics productsin Kadipaten District. The method used in this research is a survey method with descriptive and verification approaches. The population in this study were unknown users of Wardah Cosmetics productsin the Kadipaten District, so the sample in this study used simple random sampling of 100 people. The type of data used is primary data obtained from question naires that are collected for all samples. The data analysis used descriptive analysis and regression analysis including classical assumption test, multiple linear regression analysis, analysis of the coefficient of determination and model feasibility test. Hypothesis testing using the t test. The results of descriptive analysis show that Marketing Based on Experience, Perceived Quality,Advertising and purchase decisions have good criteria. The results of the verification analysis show that partially the Experimental Marketing, Perceptions of Qualityand Advertising have a positive and significant effect on purchasing decisions for users of Wardah Cosmetics productsin Kadipaten District.